2016
DOI: 10.1016/j.ydbio.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The brain expressed x-linked gene 1 (Bex1) regulates myoblast fusion

Abstract: Skeletal muscle development (myogenesis) is a complex but precisely orchestrated process involving spatiotemporal regulation of the proliferation, differentiation and fusion of myogenic progenitor cells (myoblasts). Here we identify brain expressed x-linked gene 1 (Bex1) as a transient, developmentally regulated gene involved in myoblast fusion. Bex1 expression is undetectable in adult muscles or in quiescent muscle stem cells (satellite cells). During embryonic myogenesis, however, Bex1 is robustly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The list of the differentially regulated genes (Fig 7E and Table S2) showed that a limited set of transcripts were either induced or repressed in the presence of GDF3. Several of the differentially regulated genes, including Bex1, (Jiang et al, 2016; Koo et al, 2007), Sgca (Matsumura et al, 1992) and Camk1g, have been implicated in muscle regeneration, muscle structure and/or Ca 2+ homeostasis, showing that macrophage derived GDF3 could elicit biologically relevant changes during muscle regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…The list of the differentially regulated genes (Fig 7E and Table S2) showed that a limited set of transcripts were either induced or repressed in the presence of GDF3. Several of the differentially regulated genes, including Bex1, (Jiang et al, 2016; Koo et al, 2007), Sgca (Matsumura et al, 1992) and Camk1g, have been implicated in muscle regeneration, muscle structure and/or Ca 2+ homeostasis, showing that macrophage derived GDF3 could elicit biologically relevant changes during muscle regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…The interplay between death and differentiation signaling is becoming increasingly appreciated (64,(94)(95)(96). Our results showed that Bex1 is highly expressed in early stages of myocardial development and that Bex1 and Tceal8 inhibited cell death in response to ectopic E2f2.…”
Section: Discussionmentioning
confidence: 56%
“…The endogenous function of Bex/Tceal family proteins are largely unknown, but previous work has shown their role in other cell types such as neuronal differentiation (63) and skeletal myoblast maturation (64,65). BEX1 has been shown to regulate NGF signaling in neurons by altering its activity on p75 NTR and trkA.…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous function of Bex/Tceal family proteins are largely unknown, but previous work has shown their role in other cell types such as neuronal differentiation 62 and skeletal myoblast maturation 63,64 . BEX1 has been shown to regulate NGF signaling in neurons by altering its activity on p75 NTR and trkA.…”
Section: Discussionmentioning
confidence: 99%